Avaliação da circulação de Orthopoxvirus em pequenos mamíferos de áreas urbanas, silvestres e rurais de Minas Gerais, Brasil - Julia Bahia Miranda (2016)
Vaccinia virus causes in Brazil a disease named Bovine vaccine and it affects mainly milking cows and cow handlers. This disease causes many economic, social and public health losses. Virus circulation clues have been obtained from many different mammals, but little is known about its natural host. Previous studies have shown that rodents are important on VACV chain transmission, fact reinforced by BeAn58058 virus isolation from a naturally infected rodent in the 60ths. In order to better evaluate VACV circulation in rodents and other small mammals, four animals collections from Minas Gerais state were studied in the present work (Sabará, Serro and Rio Pomba). Animals had their samples of serum and/or liver tested for OPV DNA presence and serum was also submitted to plaque reduction neutralizing test (PRNT). Rodents serum was additionally tested by ELISA for detection of IgG anti-OPV antibodies. Combined techniques resulted in a positivity of 17,2% for Sabará, 27,2% for Serro and 11,4% for Rio Pomba. Two animals from Contagem were positive for the urban animals collection. It was possible to detect positive samples in every tested area and it was also possible to detect viruses belonging to group I and II of Brazilian VACVs. The results reinforce the importance of rodents participation in VACV transmission chain in Brazil and they insert marsupials as possible links between the sylvatic environment and peridomicile, place where bovines can be infected and BV outbreaks can start. Further studies are necessary for better understanding the impact of VACV detection in urban environments, since any case of BV has ever been detected in these places.